Assessing Rangeland Suitability for Livestock Production in Pastoral Areas of Afar Ethiopia: Multi-Criteria Model Analysis in GIS and Remote Sensing (International Journal of Veterinary Medicine and Animal Science, 2024)
Humans benefit significantly from rangelands in terms of both economic and environmental aspects. However, climate variability and anthropogenic causes can hurt rangeland production. Rangeland suitability analysis is a critical step in rangeland management. The study sought to analyze the feasibility of rangelands for livestock production in agro-pastoral areas of Afar, Ethiopia’s pastoral regions. Natural pasture was the predominant feed source for animals, and feed shortage was the primary obstacle to livestock productivity, followed by drought in pastoral and agro-pastoral systems, respectively. The five suitability parameters assessed were altitude, land use or land cover, soil, water availability, and slope. ArcGIS 10.7.1 was used to process vector and raster data layers. Finally, suitability classes were determined by conducting a weighted overlay of spatial analysis, which relied on the reclassified raster layer incorporating all parameters, along with the outcomes of multicriteria analysis. The study’s outcomes revealed that 1.20%, 8.49%, 20.08%, 69.26%, and 0.95% of the study area were categorized as highly suitable, moderately suitable, marginally suitable, presently unsuitable, and permanently unsuitable for cattle production, respectively